THE ROLE OF ENTREPRENEURIAL CHARACTERISTIC ON ENTREPRENEURIAL INTENTION - Wahyudono, Denny Bernardus Kurnia (JMBI UNSRAT (Jurnal Ilmiah Manajemen Bisnis dan Inovasi Universitas Sam Ratulangi)., 2023)
The Theory of Planned Behaviour put forward by Ajzen says that to influence entrepreneurial intentions, there are several factors, namely attitudes towards entrepreneurship, subjective norms, and perceived behavioural control. This study aims to analyse how the influence of entrepreneurial characteristics influences entrepreneurial intention. Derivative entrepreneurial characteristics include sociability, planning, leadership, innovation, and risk-taking. The sample of this study were Business School Students at Universitas Ciputra in Surabaya who had taken Entrepreneurship courses up to semester 6 of 190 respondents. The data that has been collected is processed using SEM-PLS. This study concludes that not all elements in entrepreneurial characteristics significantly influence students’ entrepreneurial intentions. This is because many students still need clarification about planning the career path they will take in the future.